Blockchain for the future of sustainable supply chain management in Industry 4.0 - Esmaeilian, Behzad; Sarkis, Joe; Lewis, Kemper; Behdad, Sara (Resources, conservation and recycling, 2020)
•An overview of Blockchain and Industry 4.0 is provided.•The abilities of Industry 4.0 for advancing sustainable supply chains are discussed.•Four capabilities of blockchain towards sustainable supply chain management are described.•The design of incentive mechanisms to promote consumer green behavior is elaborated.•Reduction of operational costs and improvement of sustainability monitoring are discussed. The objective of this study is to provide an overview of Blockchain technology and Industry 4.0 for advancing supply chains towards sustainability. First, extracted from the existing literature, we evaluate the capabilities of Industry 4.0 for sustainability under three main topics of (1) Internet of things (IoT)-enabled energy management in smart factories; (2) smart logistics and transportation; and (3) smart business models. We expand beyond Industry 4.0 with unfolding the capabilities that Blockchain offers for increasing sustainability, under four main areas: (1) design of incentive mechanisms and tokenization to promote consumer green behavior; (2) enhance visibility across the entire product lifecycle; (3) increase systems efficiency while decreasing development and operational costs; and (4) foster sustainability monitoring and reporting performance across supply chain networks. Furthermore, Blockchain technology capabilities for contributing to social and environmental sustainability, research gaps, adversary effects of Blockchain, and future research directions are discussed.